ERGONOMIC AND BIOMECHANICAL ANALYSIS FOCUSED ON THE MANAGEMENT OF MAINTENANCE AND PUBLIC CLEANING SERVICES - NICKEL, Elton Moura; MORO, Antônio; MERINO, Eugenio; FORCELLINI, Fernando; GOMES FERREIRA, Marcelo (Human Factors in Design, 2012)
<!– /* Font Definitions */ @font-face font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:auto; mso-font-pitch:variable; mso-font-signature:3 0 0 0 1 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin-top:0cm; margin-right:0cm; margin-bottom:10.0pt; margin-left:0cm; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-ansi-language:PT-BR; p.Abstract, li.Abstract, div.Abstract mso-style-name:Abstract; margin-top:0cm; margin-right:0cm; margin-bottom:4.0pt; margin-left:0cm; text-align:justify; mso-pagination:widow-orphan; font-size:10.0pt; mso-bidi-font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-ansi-language:PT-BR; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> This article presents the results related to an Ergonomic Work Analysis carried out with street sweepers in the city of Florianópolis/SC, Brazil. The RULA Protocol, by McAtamney & Corlett (1993), as well as the study of Inertial Properties of the Body, by Riehle (1979), were used as tools of ergonomic and biomechanical analysis, in order to subsidize proposals to improve the management of the working environment analyzed.